The phenomenon of media violence: Historical and philosophical genesis - M.A. Marzan (Ученые записки Казанского университета: Серия Гуманитарные науки)
Violence has special importance in the history of world civilization because of its ambivalent nature. That is why the entire humankind aims to have creation, harmony, liberty, but this is disrupted by destruction, disharmony, and suppression. Therefore, there is a contradictory duality in the understanding of violence. In this article, the author has examined the occurrence and transformation of violence in three historical forms (myths, religion, and science), presented the views of various philosophers of Antiquity, Medieval Ages, Renaissance, and Modern Era in accordance with the above-said forms, and shows social institutions (mythology, religion, science, government, morality) as a means for transmission of violence from one institution to another and to society as a whole. To classify the philosophical ideas, the author has used the interpretation of violent acts by A.A. Huseynov: apology of violence, radical negation, and courteous denial. Based on the results of the study, the following conclusions have been formulated: 1. In all types of historical consciousness, a pattern can be traced in the transformation of violence phenomenon from radical to courteous denial and violence justification. 2. Mythological world vision is characterized by the ideas of harmony, measure, chaos, cosmogonic plots associated with the creation of the world out of violence, aggression, murder, dismemberment, and struggle. 3. In the religious world vision, appeasement, arrangement, and nonviolence are based on the sacrificial rituals, forced rituals, and customs related to sacralization. 4. In the Renascence period, anthropocentrism and humanism appeared. The representatives of these movements criticized conflicts, wars, strife, inquisitions, scaffold executions, accepting the good, reasoning power, morals. 5. Empiricists, rationalists, irrationalists, French enlighteners, representatives of subjective idealism, and others view the phenomenon of violence from different points of view. 6. The society without violence is ideal, but the humankind aims to achieve this ideal through violence. Confrontation between violence and nonviolence is inevitable. So, this phenomenon is archaic. Nowadays, it seems to be a social problem, which requires new understanding.